2020
DOI: 10.1155/2020/3690124
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnosis and Exercise Rehabilitation of Knee Joint Anterior Cruciate Ligament Injury Based on 3D-CT Reconstruction

Abstract: The joint capsule of the knee joint is attached to the edges of various articular surfaces and is thin and loose. Therefore, ligament reinforcement is needed to protect the knee joint and increase the stability of the joint. It plays a vital role in human activities. In this paper, a 3D-CT three-dimensional reconstruction method is used to reconstruct the ACL natural femoral imprint and double-bone tract. The relative positional relationship between the two center points is compared, and the law is summarized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Compliant control is necessary to ensure patient safety. The compliance control can be classified into the category of force control, and the commonly used force control methods include impedance control, force-position hybrid control, adaptive control, and fuzzy control [ 28 ]. Impedance control is first and foremost one of the basic control methods to achieve flexible control.…”
Section: Movement Rehabilitation Control Methods Based On Artificial ...mentioning
confidence: 99%
“…Compliant control is necessary to ensure patient safety. The compliance control can be classified into the category of force control, and the commonly used force control methods include impedance control, force-position hybrid control, adaptive control, and fuzzy control [ 28 ]. Impedance control is first and foremost one of the basic control methods to achieve flexible control.…”
Section: Movement Rehabilitation Control Methods Based On Artificial ...mentioning
confidence: 99%
“…It has the advantages of less trauma, shorter operation duration, and faster postoperative recovery. Effective rehabilitation training after surgery can further consolidate the surgical effect and promote the recovery of patient knee function, but irregular functional exercise will lead to ligament relaxation or elongated ligament after reconstruction or even rupture, so that the ligament cannot play its due function and directly affect the surgical effect [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang and Lv found that postoperative functional recovery of the affected limb in hip replacement patients was closely related to perioperative intervention and functional exercise [ 14 ]. Therefore, scientific and practical nursing measures to improve the effectiveness of surgery and improve patients' prognoses have a positive role.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang and Lv found that postoperative functional recovery of the affected limb in hip replacement patients was closely related to perioperative intervention and functional exercise [14].…”
Section: Introductionmentioning
confidence: 99%